2011
DOI: 10.1007/s12029-011-9341-6
|View full text |Cite
|
Sign up to set email alerts
|

LFA-1 Expression in a Series of Colorectal Adenocarcinomas

Abstract: The positive association of LFA-1 expression in mLNs when the primary tumor site is also LFA-1(+) could imply an adaptation advantage of this specific cellular clone to its micro-environment, predisposing it to creation of mLNs, pointing to a role for LFA-1 in creation of mLNs in CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…Integrins are also important in promoting cell survival by preventing anoikis, which is apoptosis induced by anchorage-dependent cells detaching from the surrounding ECM (23,24). There has been accumulating evidence showing that integrins β-2 and β-3 have a relationship with cancer progression and migration, including HCC (2531). For example, Li et al reported that the downregulation of integrin β-3 in small cell lung cancer cells reduced cell migration/invasion and induced apoptosis (30).…”
Section: Discussionmentioning
confidence: 99%
“…Integrins are also important in promoting cell survival by preventing anoikis, which is apoptosis induced by anchorage-dependent cells detaching from the surrounding ECM (23,24). There has been accumulating evidence showing that integrins β-2 and β-3 have a relationship with cancer progression and migration, including HCC (2531). For example, Li et al reported that the downregulation of integrin β-3 in small cell lung cancer cells reduced cell migration/invasion and induced apoptosis (30).…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the mechanisms, the team performed a qRT-PCR array and the experiment result demonstrated that integrin β underwent great changes after the knock down of CTHRC1. It has been reported that integrin β2/β3 are related with tumor metastasis 51-57. Integrins, composed by α- and β-subunits, are one type of transmembrane receptors.…”
Section: The Role Of Cthrc1 In Multi-signaling Pathwaysmentioning
confidence: 99%
“…Lymphocyte Function Associated Antigen (LFA)-1 (CD11a/CD18 or α L β 2 ) is a heterodimeric protein of the integrin family expressed on the surface of nearly all leukocytes [ 5 ] and recently described on a variety of tumor cells [ 1 , 6 , 7 ] including colorectal cancer cells [ 8 , 9 ]. LFA-1 is the main ligand for intercellular adhesion molecule (ICAM)-1 [ 10 , 11 ] to which the integrin binds with the highest affinity.…”
Section: Introductionmentioning
confidence: 99%